Beyond the usual: a case of acrodermatitis enteropathica clinically resembling erythrokeratoderma variabilis - Hyder, Mohammed S.; Salam, Arisha; Inamadar, Arun C. (International Journal of Research in Dermatology, 2025)
Acrodermatitis enteropathica (AE) is an uncommon genetic condition marked by impaired zinc absorption, often presenting with skin and hair changes. An 18-year-old male came to our department with longstanding scaly skin lesions showing a migratory pattern, closely resembling erythrokeratoderma variabilis (EKV), along with universal hair loss. Symptoms had worsened after using traditional remedies. A family history of similar complaints in a sibling was noted. His serum zinc level measured 116 ng/ml. Treatment with oral zinc at 3 mg/kg showed limited improvement, which significantly increased after raising the dose to 5 mg/kg. Based on the periorificial involvement, alopecia, family history, and response to zinc, a diagnosis of AE was made. This case highlights an atypical presentation of AE mimicking EKV, emphasizing the need for high suspicion in unusual dermatoses and the importance of therapeutic response in guiding diagnosis.